Limiting permissible limitations: how to preserve the substance of religious freedom - Bielefeldt, Heiner (Religion and human rights, 2020)
The question of how to draw legitimate limits to the content and exercise of human rights has caused many controversies, not only in academic debates, but also in human rights practice. Governments often invoke limitation clauses linked to human rights provisions as a broad allowance to impose restrictions. However, the main function of those clauses is actually to limit the scope of permissible limitations. This chapter takes freedom of religion or belief as a test case to illustrate the role of limitation clauses. Moreover, from an adequate understanding of limitation clauses, the popular “balancing” semantics deserves serious criticism, since it obfuscates the task to preserve the substance of human rights guarantees even in situations of normative conflict.